Black Garlic: Kandungan Senyawa Bioaktif, dan Bioaktivitasnya - Fistara Lesti Rahmafitria; Nuniek Herdyastuti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
Black garlic is a processed garlic product (Allium sativum L.) produced through controlled heating at high temperatures and humidity for a specific period. This process causes distinctive sensory changes, including a black color, a softer texture, a sweeter flavor, and a less pungent aroma compared to fresh garlic. These thermal changes lead to chemical changes, such as a decrease in allicin and an increase in more stable bioactive compounds such as S-allyl-L-cysteine ​​(SAC), polyphenols, flavonoids, and Maillard reaction products. These compositional changes are closely related to various bioactivities of black garlic, especially antioxidant activity, followed by anti-inflammatory, antidiabetic, anticancer, antimicrobial, and cardiovascular and metabolic effects. Research reports still show high data heterogeneity due to differences in processing conditions, raw material varieties, analytical methods, and biological models used. Furthermore, available scientific evidence is still limited to analytical, in vitro, and animal studies, while clinical evidence in humans is still very limited. This article reviews the manufacturing process, physicochemical and chemical changes, bioactive content, bioactivity, and research gaps in black garlic as a basis for developing garlic-based functional foods.